Are morphokinetic parameters of embryo development associated with adverse perinatal outcomes following fresh blastocyst transfer?. Issue 1 (January 2021) - Doron-Lalehzari, Alona; Wainstock, Tamar; Szaingurten-Solodkin, Irit; Richter, Dganit; Zeadna, Atif; Harlev, Avi; Lunenfeld, Eitan; Levitas, Eliahu; Har-Vardi, Iris
Abstract: Research question: Are obstetric and perinatal complications associated with morphokinetic parameters of embryo development? Design: This proof-of-concept pilot study included a retrospective analysis of embryo morphokinetic parameters of 85 live births following day 5 single blastocyst transfer. Kinetic variables included time interval (hours) from time of pronuclei fading (tPNf) to: time of 2 cells (tPNf–t2), 9 cells (tPNf–t9), morula (tPNf–tM), start of blastulation (tPNf–tSB), full blastocyst (tPNf–tB) and expanded blastocyst (tPNf–tEB). Multivariable logistic models were used to calculate the risk of perinatal complications after adjustment for confounders. Results: The mean interval of tPNf–tSB was significantly longer for newborns with congenital anomalies compared with healthy newborns (79.49 ± 5.78 versus 71.7 ± 6.3, respectively, P  = 0.01) and for embryos of women who had gestational diabetes mellitus compared with normoglycemic women (76.56 ± 7.55 versus 71.5 ± 6.13, respectively, P  = 0.015). The mean interval of tPNf–t9 was significantly longer for low-birthweight newborns compared with normal weight (49.25 ± 5.54 versus 45.47 ± 4.77, respectively, P  = 0.01). Preterm delivery was associated with several longer intervals of cell divisions compared with delivery at term (tPNf–t5: 28.76 ± 3.13 versus 26.64 ± 2.40, respectively, P  = 0.01; tPNf–t6: 30.10 ± 3.05 versus 27.68 ± 2.30, respectively, P  < 0.001; tPNf–t7: 32.08 ± 4.11 versus 28.70 ± 2.67, respectively, P  < 0.001; tPNf–t8: 34.75 ± 4.95 versus 30.70 ± 4.10, respectively, P  < 0.001; tPNf–t9: 50.23 ± 5.87 versus 45.44 ± 4.67, respectively, P  < 0.001). For each of the outcomes, the association remained significant after adjusting for confounders. Conclusion: This study indicates that there may be a possible association between adverse perinatal outcomes and morphokinetic parameters. Larger studies are needed to establish this association.